Australia under Abbott : what it means for the region - Sam, Bateman (2014)
The incoming Abbott Government is likely to place greater emphasis on bilateral relations and be less sensitive to regional concerns than its predecessor. How will this affect Canberra’s ties with its neighbours, especially in Southeast Asia?